Feeling Ostracized by Others’ Smartphone Use: The Effect of Phubbing on Fundamental Needs, Mood, and Trust - Knausenberger, Judith; Giesen-Leuchter, Anna; Echterhoff, Gerald (Frontiers in Psychology, 2022)
With phubbing (i.e., “The act of snubbing someone … by looking at your phone instead of paying attention”) being a widespread phenomenon, a sound understanding of its emotional reverberations and consequences for interpersonal relationships is required. To the extent that phubbing is perceived as a momentary act of ostracism, it should influence both emotional and behavioral reactions. To address this issue empirically, we investigated effects of phubbing on variables previously shown to be affected by ostracism. Specifically, we examined in two studies how being phubbed affects participants’ mood, satisfaction of fundamental needs, feelings of being ostracized (Study 1 and 2) and trust (Study 2). In Study 1, participants remembered a situation in which they were either phubbed, phubbed someone else or experienced an attentive conversation. In Study 2 different phubbing behaviors were manipulated during an ongoing conversation. Results from both studies suggest that phubbing triggers negative mood and feelings of ostracism, and threatens fundamental needs. Study 2 revealed that these effects were stronger when phubbing occurred three times (vs. once). Study 2 further demonstrated behavioral consequences of phubbing, namely that trust in a trust game was reduced when participants were phubbed three times (vs. once). We discuss conceptual and practical implications of smartphone use for emotion regulation and interpersonal relations.